2022
DOI: 10.3390/antiox11030486
|View full text |Cite
|
Sign up to set email alerts
|

Role of Food Hydrocolloids as Antioxidants along with Modern Processing Techniques on the Surimi Protein Gel Textural Properties, Developments, Limitation and Future Perspectives

Abstract: Texture is an important parameter in determining the quality characteristics and consumer acceptability of seafood and fish protein-based products. The addition of food-based additives as antioxidants (monosaccharides, oilgosaccharides, polysaccharides and protein hydrolysates) in surimi and other seafood products has become a promising trend at an industrial scale. Improvement in gelling, textural and structural attributes of surimi gel could be attained by inhibiting the oxidative changes, protein denaturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 141 publications
0
18
0
Order By: Relevance
“…Protein oxidation commonly occurs in surimi-based products and can affect their texture characteristics during storage [ 7 ]. Since almost all oxidized proteins undergo carbonylation, carbonyl groups are considered reliable markers of protein oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Protein oxidation commonly occurs in surimi-based products and can affect their texture characteristics during storage [ 7 ]. Since almost all oxidized proteins undergo carbonylation, carbonyl groups are considered reliable markers of protein oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of salt-soluble protein content during frozen storage was mainly due to the formation of hydrogen bonds, disulfide bonds, and hydrophobic bonds [ 30 ]. In addition to protein denaturation caused by ice crystals, protein denaturation mediated by protein oxidation has gradually attracted attention in recent years due to the general sensitivity of myosin to reactive oxygen species [ 7 , 41 , 42 ]. The results also indicated that AE could reduce oxidation-induced changes in myofibrillar protein structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of protein gel used in food development depends on its functional and nutritional properties. In recent decades, there has been a growing need for protein-based products among individuals due to the increasing population (Henchion et al, 2017;Walayat et al, 2022b). Consumer demand for easy and ready-to-eat products is rising as new technologies are developed a notion that encompasses both the simplicity of preparation employed and the products' prolonged shelf-life (Espinosa et al, 2015).…”
Section: New Techniques Used For Surimi-based Productsmentioning
confidence: 99%